Restart of Anticoagulant Therapy and Risk of Thrombosis, Rebleeding, and Death after Factor Xa Inhibitor Reversal in Major Bleeding Patients - Milling, Truman J., Jr.; King, Ben; Yue, Patrick; Middeldorp, Saskia; Beyer-Westendorf, Jan; Eikelboom, John W.; Crowther, Mark; Xu, Lizhen; Verhamme, Peter; Siegal, Deborah M.; Connolly, Stuart J.; on behalf of the ANNEXA-4 Investigators (Thrombosis and Haemostasis, 2021)
Background Lack of data on balancing bleeding and thrombosis risk causes uncertainty about restarting anticoagulants after major bleeding. Anticoagulant reversal trials offer prospectively gathered data after major bleeding with well-documented safety events and restarting behavior.Objectives To examine the relationship of restarting anticoagulation with thrombosis, rebleeding, and death.Methods This is a posthoc analysis of a prospective factor Xa inhibitor reversal study at 63 centers in North America and Europe. We compared outcomes of restarted patients with those not restarted using landmark and time-dependent Cox proportional hazards models. Outcomes included thrombotic and bleeding events and death and a composite of all three.Results Of 352 patients enrolled, oral anticoagulation was restarted in 100 (28%) during 30-day follow-up. Thirty-four (9.7%) had thrombotic events, 15 (4.3%) had bleeding events (after day 3), and 49 (14%) died. In the landmark analysis comparing patients restarted within 14 days to those not, restarting was associated with decreased thrombotic events (hazard ratio [HR] = 0.112; 95% confidence interval [CI]: 0.001–0.944; p = 0.043) and increased rebleeding (HR = 8.39; 95% CI: 1.13–62.29; p = 0.037). The time-dependent Cox model showed evidence for a reduction in a composite (thrombotic events, bleeding, and death) attempting to capture net benefit (HR = 0.384; 95% CI: 0.161–0.915; p = 0.031).Conclusion This analysis provides modest evidence that restarting anticoagulation in factor Xa inhibitor-associated major bleeding patients is correlated with reduced risk of thrombotic events and increased risk of rebleeding. There is low-level evidence of net benefit for restarting. A randomized trial of restarting would be appropriate.
Keywords: pulmonary embolism; stroke; prevention; thrombosis; venous thromboembolism